Assessing eye orbits as predictors of Neandertal group size. Issue 4 (29th April 2015) - Traynor, Sarah; Gurtov, Alia N.; Senjem, Jess Hutton; Hawks, John
ABSTRACT Objectives The objective is to investigate the hypothesis that Neandertal eye orbits can predict group size and social cognition as presented by Pearce et al. (Proc R Soc B Biol Sci 280 (2013) 20130168). Materials and Methods We performed a linear regression of known orbital aperture diameter (OAD), neocortex ratio, and group size among 18 extant diurnal primate species. Our data were derived from Kirk (J Hum Evol 51 (2006) 159–170) and Dunbar (J Hum Evol 22 (1992), 469–493; J Hum Evol 28 (1995) 287–296). Results There is a positive correlation between OAD and group size; a positive correlation between neocortex and group size; and a positive correlation between OAD and neocortex size. The strength of the collinearity between OAD and neocortex ratio accounts for any significance of OAD in a model. The model that best accounts for variation in group size is one that includes only neocortex ratio; including OAD does not strengthen the model. OAD accounts for 29 percent of the variation in group size. Discussion Larger orbits are correlated with larger group sizes in primates, although not significantly when controlling for neocortex ratio. Moreover, the amount of variation in group size that can be explained by OAD is negligible. The larger orbits of Neandertals compared to the average modern human population do not permit any interpretation of cognitive ability related to group size. Am J Phys Anthropol 157:680–683, 2015. © 2015 Wiley Periodicals, Inc.